Answer:
-18
Explanation:
Simplify the following:
abs(3 - 10) - (12/4 + 2)^2
The gcd of 12 and 4 is 4, so 12/4 = (4×3)/(4×1) = 4/4×3 = 3:
abs(3 - 10) - (3 + 2)^2
3 + 2 = 5:
abs(3 - 10) - 5^2
3 - 10 = -7:
abs(-7) - 5^2
5^2 = 25:
abs(-7) - 25
Since -7<=0, then abs(-7) = 7:
7 - 25
7 - 25 = -18:
Answer: -18
For this case we must resolve the expression:
We have the following definitions:
Different signs are subtracted and the sign of the major is placed.
Absolute value definition:
Resolving we have:
Then, rewriting the expression:
6.5m questions
8.7m answers